1999
DOI: 10.1136/jnnp.67.6.763
|View full text |Cite
|
Sign up to set email alerts
|

BCL-2 Family protein expression in initial and recurrent glioblastomas: modulation by radiochemotherapy

Abstract: Objective-In vitro studies indicate a role of apoptosis regulatory proteins of the BCL-2 family in the resistance of glioblastoma multiforme to irradiation and chemotherapy. To date, no study has compared the expression of these proteins in initial and recurrent tumours. The diVerences of expression of BCL-2, BCL-X, BAX, and MCL-1 proteins of paired first resection and recurrence glioblastoma specimens were examined. Methods-Immunohistochemistry was performed in 37 cases of glioblastoma multiforme with paraYn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 22 publications
6
81
0
3
Order By: Relevance
“…In the progression from initial to recurrent GBM, anti-apoptotic Bcl-2 proteins are upregulated and pro-apoptotic members are downregulated. 13 In support of a role for Bcl-2 in GBM, antisense-mediated neutralization resulted in decreased cell growth in vitro; 14 however, increased Bcl-2 expression in high-grade gliomas has been shown to correlate positively with survival. 15 Bcl-x L , another anti-apoptotic family member, is upregulated as a result of overexpression of activated mutant EGFR (EGFRvIII) to increase resistance to the chemotherapeutic agent cisplatin.…”
Section: αB-crystallin Is a Novel Gliomagenic Oncoproteinmentioning
confidence: 99%
“…In the progression from initial to recurrent GBM, anti-apoptotic Bcl-2 proteins are upregulated and pro-apoptotic members are downregulated. 13 In support of a role for Bcl-2 in GBM, antisense-mediated neutralization resulted in decreased cell growth in vitro; 14 however, increased Bcl-2 expression in high-grade gliomas has been shown to correlate positively with survival. 15 Bcl-x L , another anti-apoptotic family member, is upregulated as a result of overexpression of activated mutant EGFR (EGFRvIII) to increase resistance to the chemotherapeutic agent cisplatin.…”
Section: αB-crystallin Is a Novel Gliomagenic Oncoproteinmentioning
confidence: 99%
“…Our results support this hypothesis, demonstrating a significant difference in the expression of XIAP and Bcl-2, both anti-apoptotic genes, in glioblastomas, and it can suggest that the cellular death triggered by the apoptosis intrinsic pathway was inhibited in these tumors. Strik et al, also showed that the changes in Bcl-2 family protein expression can result from radiochemotherapy, but also reflect the natural course of disease 19 . Several proteins are released from the mitochondrial intermembrane space into the cytoplasm, including cytochrome C and Smac/DIABLO.…”
mentioning
confidence: 99%
“…Fels et al (9) haviam detectado propensão similar quanto à positividade para BCL-2 nos tumores astrocíticos de alto grau (48% no grau III; 51% no IV), ao passo que Ellison et al (8) descreveram inclinação oposta (44% no grau II; 42% no III; 28% no IV). Recentemente, Strik et al (22) e Kraus et al (15) confirmaram a tendência de maior positividade entre os astrocitomas grau IV (94,6% e 60,25%, respectivamente), reforçando o perfil aqui reportado. Possíveis comparações semiquantitativas acerca da expressão de BCL-2 em tumores astrocíticos foram impossibilitadas pela inexistência de estudos anteriores de moléculas relacionadas à apoptose (10) , consolidando as diferenças entre os tumores do grau I estudados (astrocitomas pilocíticos) e os astrocitomas grau II, esses últimos sabidamente propensos à progressão para fenótipos mais malignos (13) .…”
Section: Discussionunclassified
“…Todavia essas variações podem ser mais bem compreendidas quando avaliadas ante o equilíbrio entre as tendências pró e antiapoptótica (25) . Os escassos estudos até então publicados acerca da expressão imuno-histoquímica de BAX nos tumores astrocíticos relatam apenas a alta freqüência da detecção de BAX nos glioblastomas (78% (22) , 94% (4) , 98% (14) ), diferentemente da moderada positividade reportada no presente estudo (47,62% (18) .…”
Section: Discussionunclassified